Design and implementation of high-order PID for second-order processes with time delay - Han, Wenjie; Hu, Xingqi; Damiran, Ulemj; Tan, Wen (Frontiers in Control Engineering, 2022)
In this paper, a state space pole placement approach is first proposed to design high-order PID controllers for high-order processes. The method makes use of a single parameter to determine the locations of the closed-loop poles, thus a high-order PID controller can be tuned with this parameter. To implement the high-order PID controller in practice, an observer-based PID structure is proposed. The structure utilizes a model-free observer to estimate the plant output and its derivatives, thus retains the high-order PID structure but can filter the measurement noise and make the high-order derivatives of the plant output available for control. The proposed method is applied to design high-order PID controllers for second-order processes with time delay. Simulation results show that high-order PID can indeed improve the performance of the conventional PID control for second-order processes with time delay in disturbance rejection and robustness.